EXTH-29. INHIBITION OF LYSINE-SPECIFIC HISTONE DEMETHYLASE 1A (KDM1A/LSD1) SENSITIZES GLIOBLASTOMA CELLS TO CHEMO AND RADIATION THERAPY - Alejo, Salvador (Neuro Oncol, 2020)
BACKGROUND: Despite treatment advances, glioblastoma (GBM) is the deadliest tumor of the central nervous system. Patients face a dismal 15-month median survival and average 5-year survival rate of 13%. Current standard of care includes surgical resection, external beam radiation therapy, and adjuvant chemotherapy with temozolomide (TMZ). Unfortunately, GBM patients often relapse and succumb to their disease. Recently, we have shown that lysine-specific histone demethylase 1A (KDM1A/LSD1) is overexpressed in GBM. In this study, we tested the hypothesis that KDM1A is essential for DNA damage response (DDR), inhibiting KDM1A thereby sensitizes GBM to either TMZ or radiation therapy. METHODS: KDM1A knockout (KDM1A-KO) and knockdown (KDM1A-KD) cells were generated using CRISPR/Cas9 and KDM1A specific shRNA, respectively. Cell viability, clonogenic survival, and apoptotic assays were used to study the effect of KDM1A-KO, -KD, or pharmacological KDM1A inhibitors (NCD-38 and NCL-1) on radiation and TMZ sensitization. Mechanistic studies were conducted using RNA-seq, RT-qPCR, and western blot analysis. Furthermore, in vivo efficacy of KDM1A inhibitor and TMZ was established using orthotopic models of GBM. RESULTS: Cell viability, survival, and apoptotic assays demonstrated that knockout/knockdown or inhibition of KDM1A sensitized GBM cells to both TMZ or radiation therapy. KDM1A inhibitors used in combination with radiation or TMZ significantly increased apoptosis in GBM cells. RNA-seq analysis and signaling studies showed attenuation of DDR pathways in KDM1A-KD cells. Radiation or TMZ treatment enhanced DNA damage in KDM1A-KD cells compared to controls. Importantly, combination of KDM1A inhibitor and TMZ significantly reduced in vivo tumor progression and improved overall survival in orthotopic GBM murine models. CONCLUSIONS: Our results provide strong evidence that KDM1A inhibition sensitizes GBM to TMZ or radiation therapy via modulation of DDR. This suggests combination of KDM1A inhibitors with TMZ or radiation therapy could serve as a novel treatment for GBM patients.